European consensus-based interdisciplinary guideline for melanoma. Part 2: Treatment - Update 2022 - Garbe, Claus; Amaral, Teresa; Peris, Ketty; Hauschild, Axel; Arenberger, Petr; Basset-Seguin, Nicole; Bastholt, Lars; Bataille, Veronique; del Marmol, Veronique; Dréno, Brigitte; Fargnoli, Maria C.; Forsea, Ana-Maria; et al. (European journal of cancer (1990), 2022)
A unique collaboration of multidisciplinary experts from the European Dermatology Forum (EDF), the European Association of Dermato-Oncology (EADO), and the European Organization of Research and Treatment of Cancer (EORTC) was formed to make recommendations on cutaneous melanoma diagnosis and treatment, based on the systematic literature reviews and the experts' experience. Cutaneous melanomas are excised with one to 2-cm safety margins. Sentinel lymph node dissection shall be performed as a staging procedure in patients with tumor thickness ≥1.0 mm or ≥0.8 mm with additional histological risk factors, although there is as yet no clear survival benefit for this approach. Therapeutic decisions in stage III/IV patients should be primarily made by an interdisciplinary oncology team (“tumor board”). Adjuvant therapies can be proposed in stage III/completely resected stage IV patients and are primarily anti-PD-1, independent of mutational status, or alternatively dabrafenib plus trametinib for BRAF mutant patients. In distant metastases (stage IV), either resected or not, systemic treatment is always indicated. For first-line treatment particularly in BRAF wild-type patients, immunotherapy with PD-1 antibodies alone or in combination with CTLA-4 antibodies shall be considered. In stage IV melanoma with a BRAF-V600  E/K mutation, first-line therapy with BRAF/MEK inhibitors can be offered as an alternative to immunotherapy. In patients with primary resistance to immunotherapy and harboring a BRAF-V600  E/K mutation, this therapy shall be offered as second-line therapy. Systemic therapy in stage III/IV melanoma is a rapidly changing landscape, and it is likely that these recommendations may change in the near future.